Replication of cloned DNA containing the Alu family sequence during cell extract-promoting simian virus 40 DNA synthesis. - Ariga, H (1984)
The replicating activity of several cloned DNAs containing putative origin sequences was examined in a cell-free extract that absolutely depends on simian virus 40 (SV40) T antigen promoting initiation of SV40 DNA replication in vitro. Of the three DNAs containing the human Alu family sequence (BLUR8), the origin of (Saccharomyces cerevisiae plasmid 2 micron DNA (pJD29), and the yeast autonomous replicating sequence (YRp7), only BLUR8 was active as a template. Replication in a reaction mixture with BLUR8 as a template was semiconservative and not primed by a putative RNA polymerase III transcript synthesized on the Alu family sequence in vitro. Pulse-chase experiments showed that the small-sized DNA produced in a short-term incubation was converted to full-length closed circular and open circular DNAs in alkaline sucrose gradients. DNA synthesis in extracts began in a region of the Alu family sequence and was inhibited 80% by the addition of anti-T serum. Furthermore, partially purified T antigen bound the Alu family sequence in BLUR8 by the DNA-binding immunoassay. These results suggest that SV40 T antigen recognizes the Alu family sequence, similar to the origin sequence of SV40 DNA, and initiates semiconservative DNA replication in vitro.